HUBUNGAN KONSEP DIRI DENGAN KOMPETENSI PEDAGOGIK GURU TK KECAMATAN TAMPAN KOTA PEKANBARU - Juwita Dewi Dewi; Wusono Indarto Indarto; Nurlita ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstrac: This study aims to determine the relationship of self-concept and pedagogical competence of kindergarten teachersin the district Tampan, Pekanbaru. The population inthis study amounted to127teacher fresh greaduate. The sample usedin this study were 56 teachers.As for thedata collection techniquesin this study usinga Likert scale. Analysis using scale testingand analysis of statistical methods with SPSS for Windows Ver. 16. The hypothesis of this studyis that there isa positive and significan trelation ship between self-concept and pedagogical competence of kindergarten teachersin the district Tampan, Pekanbaru. It can be seen from the analysis of data obtained tcountvalue of 7.552 while ttable(5%) (df=n-2 =56-2=54) ttablevalueby 2,000. Because tcount greater than ttable 7.552>2.000, it means that there isa positive and significan trelation ship between self-concept and pedagogical competence of kindergarten teachersin the district Tampan, Pekanbaru. The resulting of determinant coefficient wasr2= 0.393 atp = 0.000(P <0.05), it can be seen that the self-concept giving effect of39.3% of pedagogical competence of the kindergarten teacher. Keywords: Self-Concept, Pedagogic Competence.